Empowerment of Aisyiyah cadres in preventing and handling of stroke - Dian Hudiyawati; Abi Muhlisin; Tri Agustina; Wachidah Yuniartika; Wita Oktaviana; Ekan Faozi; Siti Marfu'ah; Rizki Anjarsari (Universitas Muhammadiyah Magelang, 2023)
Stroke is among the priority health issues frequently reported by the people of Gemolong, Sragen. Strokes do not only affect the elderly; individuals of productive age can also experience them. Strokes can be prevented by reducing risk factors and providing proper treatment for stroke attacks. This community service activity aims to enhance the knowledge and skills of Aisyiyah administrators in promoting stroke prevention and appropriately handling stroke attacks. The methods used in the service activities include training and simulations, encompassing socialization, education on stroke prevention and treatment, as well as stress management using Al-Quran recitations (murottals). The outcome of the service is an increased knowledge and skills of participants in prevention and treatment. This also includes cadre skills in handling stroke sequelae through bed transfer and Range of Motion (RoM), as well as implementing murottal therapy for stress management.